Characterizing changes in rainfall: a case study for New South Wales, Australia. (7th September 2017) - Hajani, Evan; Rahman, Ataur
ABSTRACT: This paper examines changes in rainfall in New South Wales (NSW), Australia using daily rainfall data from 200 rainfall stations covering the period of 1945–2014. The Mann–Kendall test is applied to identify trends in the selected rainfall indices, while the Pettitt change point test is employed to determine the direction and timing of a change point. Van Bell and Hughes homogeneity test is applied to examine homogeneity of the observed trends. It is found that the southern half of NSW is dominated by a negative trend in annual total rainfall, and autumn and spring rainfall. Based on the Pettitt change point test, it is found that annual maximum 24‐h rainfall data in NSW is dominated by a negative shift. Based on the Van Belle and Hughes method, it is found that NSW is dominated by non‐homogeneous trends in monthly maximum daily rainfall data. Overall, the results do not show any consistent pattern of rainfall trends in NSW. The findings of this study contribute towards the growing body of knowledge on the nature of changes in rainfall based on the latest data in NSW. Abstract : Locations of the selected 200 daily stations in NSW, Australia.